The Responsibilities of Notaries Who Participated in the Crime of Certificate Embezzlement - Budi, Anita Widyaningrum; Hafidz, Jawade (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
This study aims to analyze: 1) The responsibility of a notary who participates in the crime of certificate embezzlement. 2) Juridical implications for deeds issued by notaries participating in the crime of certificate embezzlement The approach used in this study is a sociological-juridical approach. The specification of the research used is descriptive analytical research. Types of data using primary data and secondary data obtained through interviews and literature. The data analysis method used in this research is descriptive analysis. The results of the study concluded: 1). Responsibilities of Notaries who participated in committing the crime of certificate embezzlement in Samarinda City were sentenced to 3 months in prison. Notary MS was legally and convincingly proven guilty of committing the crime of participating in embezzlement and fulfilling the elements in Article 372 of the Criminal Code juncto article 55 paragraph 1 of the Criminal Code. This proves that notaries are not above the law, notaries are the same as ordinary people who must comply with laws and regulations. 2) The juridical implication of the deed issued by a notary who participated in the crime of embezzlement of certificates in Samarinda City, namely that the DA as the legal owner can apply for the cancellation of the deed of sale and purchase and certificates to the Court. The filing for annulment aims to maintain legal certainty and certainty of the rights to his land. The imposition of a criminal sentence against Notary MS does not necessarily mean that the deed in question becomes null and void by law. Keywords: Criminal; Embezzlement; Liability.